Photocatalytic Spirocyclization of 2-Alk-ω-enyl-Substituted Cycloalkane-1,3-diones - Hofer, Johannes; Pecho, Franziska; Bach, Thorsten (Synlett, 2023)
When irradiated with visible light, various cyclic 2-alk-4-enyl-substituted 1,3-diketones undergo an intramolecular endo-addition (m = 1) onto the double bond resulting in spirocyclic products (11 examples, 62–92% yield). Both an organic (TXT: thioxanthone, 20 mol%) and an organometallic Ir-based photocatalyst (5 mol%) promote the reaction. Addition of triisopropylthiophenol is required to secure high yields. The spirocyclization of a 2-alk-5-enyl-substituted substrate (m = 2) delivers a mixture of the seven-membered endo- and the six-membered exo-cyclization products.
Keywords: catalysis; cyclization; electron transfer; iridium; photochemistry; radical reaction